Pedophilia in the Netherlands: causes, consequences, moral judgment - Kobyliński, Andrzej (Studia Ecologiae et Bioethicae, 2017)
The main purpose of this article is to analyze the phenomenon of pedophilia in the Netherlands and to present the most important ethical and legal aspects of child sexual abuse. It seems that in this country there has been a kind of social feedback: on the one hand, the sexual revolution of the 1960s, a process of deep secularization of Dutch society, and the birth of a new morality have created fertile ground for the development of the phenomenon of pedophilia, on the other – a drama of sexual abuse of minors contributed to even deeper breakdown of the traditional understanding of morality and religion, causing the gradual collapse of the Catholic Church and other Christian denominations. There is a bulk of information about pedophilia in the Netherlands in a special report published by the Wim Deetman’s Inquiry Commission in 2011. The drama of child sexual abuse in this country is a small part of a big phenomenon on a global scale. The key issue in this dispute about child sexual abuse is a reliable philosophical argumentation, which draws attention to the moral evil and its inclinations of the sexual relationship between adults and children.